The dynamic interplay between burnout and sleep among elite blind soccer players. (July 2018) - Li, Chunxiao; Ivarsson, Andreas; Stenling, Andreas; Wu, Yandan
Abstract: The dynamic pattern between burnout and sleep among athletes is unknown. This longitudinal survey examined the interplay between burnout and sleep among blind elite soccer players. China national blind soccer team players ( n  = 10) completed measures on burnout and sleep quality through interview at baseline (month 1), and followed at months 2, 3, 4, and 5. The results of dynamic p-technique analysis, using Bayesian estimation, showed a credible relationship between burnout and sleep quality. Also, burnout had a credible lagged effect on subsequent sleep quality whereas sleep quality did not have a credible lagged effect on burnout. The results suggest that burnout and sleep are not reciprocally related and burnout may be a risk factor of sleep problems among athletes. Highlights: There was a credible relationship between burnout and sleep quality. Burnout had a credible lagged effect on subsequent sleep quality. Sleep quality did not have a credible lagged effect on burnout.